Voltage dependence of K(+) channels in guard-cell protoplasts - Schroeder, Julian I. (1987)
Stomatal pores in leaves enable plants to regulate the exchange of gases with their environment. Variations of the pore aperture are mediated by controlled changes of potassium salt concentrations in the surrounding guard cells. The voltage-dependent gating of K(+)-selective channels in the plasma membrane (plasmalemma) of cell-wall-free guard cells (protoplasts) was studied at the molecular level in order to investigate the regulation of K(+) fluxes during stomatal movements. Inward and outward K(+) currents across the plasmalemma of guard cells were identified by using the whole-cell configuration of the patch-clamp technique. Depolarizations of the membrane potential from a holding potential of -60 mV to values more positive than -40 mV produced outward currents that were shown to be carried by K(+). Hyperpolarizations elicited inward K(+) currents. Inward and outward currents were selective for K(+) over Na(+) and could be partially blocked by exposure to extracellular Ba(2+). In cell-attached and excised membrane patches, previously identified K(+)-selective single channels in guard cells were studied. Averaging of single-channel currents during voltage pulses resulted in activation and deactivation kinetics that were similar to corresponding kinetics of inward and outward currents in whole cells, showing that K(+)-selective channels were the molecular pathways for the K(+) currents recorded across the plasmalemma of single guard-cell protoplasts. Estimates demonstrate that K(+) currents through the voltage-gated K(+) channels recorded in whole guard cells can account for physiological K(+) fluxes reported to occur during stomatal movements in leaves.